Implementation Of Balanced Scorecard In Measuring Employee Performance In The Public Sector - Fitriani; Haliah, Haliah; Kusumawati, Andi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
Balanced scorecard is one approach used to measure the performance of a company's operations, especially in Human Resources. This study aims to find out how effective the Balaced Scorecard method is in public sector companies. As we all know that the Balanced Scorecard is an analytical tool to determine employee performance and has 4 effectiveness, namely customer perspective, learning finance and growth. In this study the method applied is qualitative, while the analytical technique used is descriptive qualitative. The use of the Systematic Literature Review (SLR) method is carried out by reviewing and identifying journals systematically which in each process are reviewed and analyzed to find out how efficient and effective the Balanced Scorecard approach is used as a measurement in an effort to determine the performance of an employee in the scope of the Public Sector. The nature of this study is descriptive analysis, then elaboration / description so as to produce accurate information for future researchers. The results showed that employee training is very effective in measuring a company's performance through the Balaced Scorecard method to improve the realization of the organization's vision and mission.